PERBANDINGAN PERILAKU PEMAHAMAN LITERASI KEUANGAN MAHASISWA KEUANGAN AKUNTANSI SYARIAH DENGAN TADRIS MATEMATIKA IAIN SALATIGA - HANNA SHAVIRA; TIAS WAHYU RAMADHANTY; LUTFI ADE YULIANTI; ADELIA OCTAVIANI; FERDIYANTO (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
This study discusses how to study the financial literacy of sharia accounting students with the Salatiga IAIN mathematical tadris and the impacts arising from every financial management of Salatiga IAIN students. The method of discussion used is discussion, with quantitative descriptive research specifications. This study uses data collection techniques based on primary data through questionnaires. The population in this study were Salatiga IAIN students. The sample in this study were students of Islamic accounting and mathematics TAIN IAIN Salatiga. The results of this study indicate facts about finance on student economics and non-economics which show differences in student financial behavior..